Analysis Of Improving The Quality Of Local Government Financial Reports Through Human Resource Competence And Accounting System Integration - Davis Pratama Malau; Renny Maisyarah; Nina Andriany Nasution (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze a model for improving the quality of local government financial reports through human resource competency, the application of accounting standards, and accounting information systems. This study uses a quantitative approach with primary data obtained through the distribution of questionnaires to 60 respondents who are Civil Servants (PNS) financial coordinators in Regional Work Units (SKPD). The data analysis method used is multiple linear regression with prior data quality testing and classical assumption testing. The results show that all research instruments are valid and reliable. The classical assumption test also shows that the data are normally distributed and there is no multicollinearity. Partially, human resource competency, the application of accounting standards, and accounting information systems have a positive and significant effect on the quality of local financial reports. Simultaneously, these three variables also have a significant effect with a coefficient of determination (R²) of 0.646, indicating that 64.6% of the variation in financial report quality can be explained by the independent variables in this study. Thus, it can be concluded that improving the quality of local government financial reports can be done through improving human resource competency, implementing good accounting standards, and optimizing accounting information systems.